Features of the welded seam material crystalliza-tion in Ti-TiB alloy under electron-beam welding conditions - Petro Loboda; Volodymyr Zvorykin; Constantine Zvorykin; Eduard Vrzhyzhevskyi; Tatjana Taranova; Valery Kostin; Leonid Zvorykin (Mechanics and Advanced Technologies, 2023)
Natural metal composite materials represent a promising class of modern structural materials that need to be welded. Such materials can be welded by fusion, as has been established with the Ti-TiB alloy as an example. The enhanced operational properties of such materials are determined by the microstructure, which is characterized by the presence of microfibers of borides, carbides, or silicides in the metal matrix. To preserve the mechanical properties of materials in a welded joint, it is necessary to ensure the formation of reinforcing microfibers in the welded seam material. Determination of formation mechanism of boride microfibers, originated in the welded seam material, will become the basis for optimizing of fusion welding modes, in particular, electron beam welding mode.